Isolation, density purification, and invitro culture maintenance of functional caprine islets of Langerhans as an alternative islet source for diabetes study - Hani, Homayoun; Tengku Ibrahim, Tengku Azmi; Othman, Abas Mazni; Mohd Lila, Mohd Azmi; Allaudin, Zeenathul Nazariah (John Wiley & Sons, 2010)
Background : Insufficient availability of human donors makes the search for alternative source of islet cells mandatory for future developments in pancreatic transplantation. The present study investigates the potential of caprine as an alternative source of pancreatic islets. The objectives of the study were to optimize techniques for caprine islet isolation and purification for culture establishment, and to subsequently assess their viable and functional potential.